The fountains of silence : a novel - Sepetys, Ruta (New York : Philomel Books, 2019)
At the Castellana Hilton in 1957 Madrid, eighteen-year-old Daniel Matheson connects with Ana Moreno through photography and fate as Daniel discovers the incredibly dark side of the city under Generalissimo Franco's rule.
Keywords: Franco, Francisco, -- 1892-1975 -- Fiction; Dictatorship -- Fiction; Hotels, motels, etc. -- Fiction; Photography -- Fiction; Secrets -- Fiction; Spain -- History -- 20th century -- Juvenile fiction; Madrid (Spain) -- History -- Fiction; Spain -- History -- 20th century -- Fiction